Analisis Usahatani dan Nilai Tambah Bunga Melati Putih (Jasminum sambac) di Kecamatan Kandeman Kabupaten Batang - Tabita Tri Utami; Liska Simamora (CV Putra Publisher, 2023)
In order to increase the bargaining power of farmers and gain profits, it is necessary to shorten the trading chain and cultivate white jasmine flowers produced by the